1998
DOI: 10.1021/tx9702042
|View full text |Cite
|
Sign up to set email alerts
|

Application of Gas Chromatography/Electron Capture Negative Chemical Ionization High-Resolution Mass Spectrometry for Analysis of DNA and Protein Adducts

Abstract: The analytical potential of gas chromatography/electron capture negative chemical ionization high-resolution mass spectrometry (HRMS) for characterization and quantitation of DNA and hemoglobin adducts was demonstrated using three model compounds: N2, 3-ethenoguanine (EG), 7-(2-hydroxyethyl)guanine (7-HEG), and N-(2-hydroxyethyl)valine (HEV). At a resolving power of 10 000, the signal-to-noise (S/N) ratios obtained from quantitative selected ion monitoring (SIM) experiments using biological samples were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…This demonstrated that the increase in MS resolution power to 10,000 would lead to a narrower mass window to reduce chemical noise and analyte signal simultaneously. But, HRMS analysis still achieved similar or even better sensitivity than the GC/ ECNCI-MS SIM (Ranasinghe et al, 1998). Further studies showed that the derivatization of DNA samples with PFBBr led to the formation of the undesirable interferences, most likely due to the free purine bases released from neutral thermal hydrolysis of DNA (Kao & Giese, 2005).…”
Section: Analysis Of Ethylene Oxide-induced Molecular Dosimeters Withmentioning
confidence: 98%
See 3 more Smart Citations
“…This demonstrated that the increase in MS resolution power to 10,000 would lead to a narrower mass window to reduce chemical noise and analyte signal simultaneously. But, HRMS analysis still achieved similar or even better sensitivity than the GC/ ECNCI-MS SIM (Ranasinghe et al, 1998). Further studies showed that the derivatization of DNA samples with PFBBr led to the formation of the undesirable interferences, most likely due to the free purine bases released from neutral thermal hydrolysis of DNA (Kao & Giese, 2005).…”
Section: Analysis Of Ethylene Oxide-induced Molecular Dosimeters Withmentioning
confidence: 98%
“…To eliminate the noise and to improve the quality of quantification, GC/ECNCI-HRMS with resolution at 10,000 was used to quantify PFPTH-HEV (Ranasinghe et al, 1998). GC/ECNCI-HRMS full-scan analysis of the PFPTH-HEV derivative revealed the two major fragment ions at m/z ¼ 348.0556 (-HF) and m/ z ¼ 318.0450 due to further loss of CH 2 O and m/z ¼ 352.0830 by loss of HF and 320.0573 due to further loss of CD 2 O from the corresponding deuterium-labeled HEV derivative.…”
Section: Gc/hrms Analysis Of Eo-induced Protein Adductsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, nuclear magnetic resonance suffers from a requirement for considerably more sample amount than does MS. MS is especially useful if coupled with a separation scheme such as TLC (28), HPLC (29,30), capillary electrophoresis (CE) (31)(32)(33), capillary electrochromatography (CEC) (34), or gas chromatography (35), although this latter technique usually requires derivatization, which introduces other analysis problems (36). However, when MS monitors only selected ions or reactions, although its sensitivity is considerably enhanced, its identification powers are sharply reduced.…”
mentioning
confidence: 99%